Molecular engineering of conjugated polymers for efficient hole transport and defect passivation in perovskite solar cells. (March 2018) - Cai, Feilong; Cai, Jinlong; Yang, Liyan; Li, Wei; Gurney, Robert S.; Yi, Hunan; Iraqi, Ahmed; Liu, Dan; Wang, Tao
Abstract: Organic-inorganic hybrid perovskite solar cells represent an exceptional candidate for next-generation photovoltaic technology. However, the presence of surface defects in perovskite crystals limits the performance as well as the stability of perovskite solar cells. We have employed a series of carbazole and benzothiadiazole (BT) based donor-acceptor copolymers, which have different lengths of alkoxy side-chains grafted on the BT unit, as the dopant-free hole transport materials (HTMs) for perovskite solar cells. We demonstrate that although these side-chains can reduce the π−π stacking structural order of these copolymers to affect the hole transport properties, the methoxy unit introduces a desired defect passivation effect. Compared to the Spiro-OMeTAD-based device, the copolymer with methoxy side-chains on the BT unit (namely PCDTBT1) as the HTM achieved superior power conversion efficiency and stability due to efficient hole transport and the suppression of trap-induced degradation, whilst the copolymer with octyloxy side-chains on the BT unit (namely PCDTBT8) as the HTM lead to poor performance and stability. Graphical abstract: A series of carbazole and benzothiadiazole (BT) based copolymers have been employed as the dopant-free hole transport materials (HTMs) for perovskite solar cells. The side-chains of these HTM can reduce the π−π stacking structural order but can also introduce desired defect passivation effect.fx1 Highlights: Perovskite solar cells with PCEs over 19% were achieved using dopant-free HTMs. The thiophene and methoxy units introduce a desired defect passivation effect. PCDTBT1 passivates surface defects of perovskite and suppresses charge recombination.